OPTIMALISASI MEDIASI NON-LITIGASI SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA DALAM BIDANG PERTANAHAN - Maylesta, Nabil Rantisi (Asosiasi Dosen Hukum Acara Perdata (ADHAPER), 2024)
Abstract Land disputes constitute one of the most complex forms of civil disputes, as they involve private law relations, state administrative authority, and broader social and economic interests. In Indonesian civil justice practice, the resolution of land disputes through litigation often requires a prolonged process, incurs high costs, and risks exacerbating conflicts between the parties. Consequently, non-litigation mediation has developed as a pre-adjudicative mechanism aimed at facilitating amicable settlement prior to judicial examination. This article examines the implementation of non-litigation mediation in the resolution of land disputes in Indonesia and compares it with land mediation practices in Germany. The research employs a normative juridical method, utilizing statutory and comparative law approaches. The findings indicate that Indonesia positions land mediation as an administrative instrument integrated with state authority to maintain orderly land administration, whereas Germany emphasizes mediation as a civil dispute resolution mechanism characterized by professional independence. This article argues that the optimization of land dispute mediation in Indonesia should be directed toward strengthening the quality and professionalism of the mediation process, while preserving the administrative role of the state in ensuring legal certainty and order in land administration. Keywords: mediation; land disputes; non-litigation dispute resolution; civil procedure law; comparative law Abstrak Perlindungan hukum terhadap pembela HAM di Indonesia berada di titik yang mengkhawatirkan. Penelitian socio legal ini ini fokus terhadap kondisi objektif perlindungan hukum pembela HAM serta perlindungan hukum terhadap pembela HAM dalam perspektif teori tentang alasan penghapus pidana. Hasilnya, pembela HAM masih mengalami penangkapan, penembakan, dan penyiksaan dan masih ditemukan beberapa kebijakan hukum pidana yang justru berpotensi melanggar hak dan jaminan perlindungan hukum terhadap pembela HAM. Kedua, “the theory of lesser evils” dapat digunakan sebagai dasar untuk memberikan perlindungan hukum terhadap pembela HAM. Sepanjang perbuatan pembela HAM itu untuk melaksanakan Pasal 67 UU No. 32 Tahun 2009, misalnya, maka pembela HAM dapat dipandang sedang “melaksanakan peraturan perundang-undangan” dan dilindungi oleh Pasal 66 UU No. 32 Tahun 2009, sehingga Pasal 50 KUHP dapat diterapkan sebagai alasan penghapus pidana. Ke depan, pedoman pemidanaan terhadap pembela HAM tatkala berhadapan dengan proses penyelesaian perkara pidana juga diperlukan sebagai perlindungan hukum. Kata Kunci: Perlindungan Hukum, Pembela HAM, Alasan Penghapus Pidana